Seroprevalence Study of Human Immunodeficiency Virus, Hepatitis B Virus and Hepatitis C Virus in Humans and Risk Factors in Suleja, Nigeria - Bello, Z.; Abalaka, M.E.; Mawak, J.D. (UMYU Journal of Microbiology Research)
The study was undertaken to determine the seroprevalence of human immunodeficiency virus, hepatitis B virus (HBV) and hepatitis C Virus (HCV) infection among adults 15 years and above in Suleja, Nigeria in order to obtained the base line information on disease burden, and to assess the possible risks factors associated with these infection in the study population, A total of 360 samples were screened for the virus infection after obtaining their consent. Sera obtained from the sample were screened using rapid Immunochromatographic test kits to determine the HIV and the presences of hepatitis B surface antigen (HBs Ag) and antibody to hepatitis (Anti HCV) Respectively. The CD4+ of the entire HIV positive sample and 50 HIV negative samples were determined making use of cyslow counter according to the manufacture’s instruction. Out of the 360 sera samples tested, 58 (16.11%) were seropositive for HIV 1/2, 22 (6: 11%) were positive HBs Ag and 14(3:89%) were positive for HIV 1/2 :22 positive for both HIV and HBsAg and 5 (8:62%) were seropositive for HIV and antibody to hepatitis C (HCV) the highest prevalence of HIV 15(32:61) was in age group 35-39 results also show that the prevalence of HIV and HBV increased with age to age 35-39 and 30-34 respectively but later decrease with further increase in age. More than half of the HIV positive samples 48(69.57%) were having CD4 count < 600 cell/ul. There was slight difference associated between the risk factors, history of blood transfusion, history of sexually transmitted infection use of sharp object and Injection drug user investigated in this study and infection. Universal screenings of HIV, HBsAg and anti HCV, health education to reduce the risk of infection are suggested.